1983
DOI: 10.1080/10862968309547495
|View full text |Cite
|
Sign up to set email alerts
|

Differential Word Knowledge and Reading Comprehension

Abstract: Abstract. This study examined the effects of vocabulary pre-instruction on reading comprehension. Two vocabulary training treatments, chosen on the basis of a theoretical framework for vocabulary instruction, and a control were used with 28 average fifth-grade readers. For two of three order groups, both training treatments produced significantly higher scores on passage tests, and, for all children, both training treatments produced significantly higher scores on two sentence comprehension measures and a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1
5

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 32 publications
1
57
1
5
Order By: Relevance
“…Relying on a dictionary as the primary way to increase vocabulary does not work because good readers do not think about the definition of individual words as they read (Hague, 1987). Another way of saying this is that mere definitional knowledge is not used in the process of comprehending text (Stahl, 1983).…”
Section: Dictionary Usementioning
confidence: 99%
“…Relying on a dictionary as the primary way to increase vocabulary does not work because good readers do not think about the definition of individual words as they read (Hague, 1987). Another way of saying this is that mere definitional knowledge is not used in the process of comprehending text (Stahl, 1983).…”
Section: Dictionary Usementioning
confidence: 99%
“…Most of this research has examined the effects of various direct instructional approaches on vocabulary acquisition and certain related comprehension measures (Beck, Perfetti, & McKeown, 1982;Gipe, 1987-79;Jenkins, Pany, & Schreck, 1978;Lieberman, 1967;Mezynski, 1983;McKeown, Beck, Omanson, & Perfetti, 1983;MeKeown, Beck, Omanson, & Pople, 1985;Stahl, 1983;Stahl & Fairbanks, 1986). However, others have suggested that, because of the magnitude of the task, direct instruction can only account for a small proportion of vocabulary growth, and a substantial amount of lexical meanings must be acquired incidentally through exposure to natural written contexts (Nagy & Anderson, 1984;Nagy & Herman, 1984;Nagy, Herman, & Anderson, 1985).…”
mentioning
confidence: 99%
“…Além disso, vários autores têm mostrado, especialmente com relação à leitura na língua estrangeira, que um aperfeiçoamento na compreensão leitora pode ser atribuído a um aumento no conhecimento de vocabulário (BECK; PERFETTI; MCKEOWN, 1982;STAHL, 1983;GRABE;STOLLER;1997).…”
Section: Introductionunclassified